APPAREL PRODUCT DISSATISFACTION AND THE POST-COMPLAINT PROCESS - Kincade, Doris H; Redwine, Ann; Hancock, Gregory R (International journal of retail & distribution management, 1992)
Examines the consumer behaviours which result when an apparel product fails and the situations of seeking, receiving, and satisfaction with redress, in relation to the consumer′s intent to repurchase a brand and to revisit a store. Results indicate a definite relationship and have direct financial implications for retailers and apparel manufacturers.